Influência da adição de Pseudomonas putida no bacterioma do ninho de espuma de Leptodactylus vastus: uma nova abordagem com potencial para a conservação de anuros - Costa, Vanessa Ariane Silva da (2024)
Anurans are currently the most threatened group of vertebrates due to factors such as climate change, fragmentation, habitat loss, and infectious diseases, such as chytridiomycosis caused by the pathogenic fungus Batrachochytrium dendrobatidis (Bd). Given the severity of this disease, various studies and mitigation efforts have been pursued. So far, the most promising approach is considered to be the introduction of probiotics capable of producing anti-Bd metabolites into the skin of anurans, previously isolated from the skin of these animals. However, bacteria with anti-Bd activity can also be found in other locations such as foam nests, which are highly complex structures that serve as protection for offspring. Despite their poorly characterized microbiota, several indications show that part of the nest microbiome may compose the skin microbiome of tadpoles and young adults, which opens up possibilities for new uses of probiotics. Thus, this project proposes to analyze the antifungal and anti-Bd potential of three bacteria from foam nests, belonging to the genus Pseudomonas, already associated in the literature with anti-Bd action, and the impact of inoculating one of these microorganisms on the bacteriome of foam nests of Leptodactylus vastus, in order to shed light on new possibilities for the use of anti-Bd probiotics in nature. For this, the genomes of the three Pseudomonas strains were sequenced, and species-level identification was performed using housekeeping genes. The strain’s genomes were evaluated for the presence of genes related to antifungal activity, virulence, and pathogenicity. One of the strains was used to perform an in vitro bioaugmentation assay in natural foam nests of L. vastus. For the assay evaluation, 16S rRNA amplicon libraries of the samples from 1 and 10 days were prepared. The libraries were sequenced by NGS, and the effect of adding the bacteria on the bacterial community was assessed. The three sequenced strains were determined to be Pseudomonas putida. It was not possible to detect genes related to antibiotic resistance and pathogenicity. Regarding antifungal activity, the P. putida P119 isolate showed the highest genetic potential. No significant changes in the structure of the bacterial community were observed with the addition of the bacteria; however, a change in the network interaction profile was detected, in which P119 demonstrated compatibility and participation with the nest bacterial community. This is a first study aimed at understanding the response of foam nests to the introduction of a probiotic, expanding the range of chytridiomycosis prophylaxis possibilities.